Determinan Entrepreneurial Intention pada Mahasiswa Perguruan Tinggi Swasta (PTS) di Jakarta Barat - Tinjung Desy Nursanti; Masruroh Masruroh; Laksmi Sito Dwi Irvianti (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2019)
This study aims to analyze the factors that influence the desire for entrepreneurship (entrepreneurial intention) for students who have obtained courses in entrepreneurship or have even chosen specialization courses in entrepreneurship. It is indicated that there are three variables that influence entrepreneurial intention, namely entrepreneur program education, perceived feasibility and perceived desirability. The analysis used in this study is multiple regression. The populations of this study are students in three excellent PTS in the West Jakarta area. The results of this study indicate that of the three independent variables proposed, educational programs and perceived feasibility show a positive but not significant effect on entrepreneurial intention. Meanwhile, there is only one independent variable that influences entrepreneurial intention positively and significantly that is perceived desirability.